2012
DOI: 10.1021/ma301494c
|View full text |Cite
|
Sign up to set email alerts
|

Online Coupling of Two-Dimensional Liquid Chromatography and NMR for the Analysis of Complex Polymers

Abstract: For the first time, comprehensive two-dimensional liquid chromatography (2D-LC) of complex polymers is coupled online to 1H NMR. 2D-LC is used to separate mixtures of poly(ethylene oxide)s with regard to chemical composition and molar mass. The present samples contain polymers with different end groups and chain distributions. In the first LC dimension, liquid chromatography at critical conditions (LCCC) is used for the selective separation according to the end groups. Fractions that are then uniform regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Yet, an enormous potential of this technique becomes obvious when considering the hyphenation of 2D HT‐LC (or HT‐LC) systems with post separation characterization. A direct benefit lies in the on‐line hyphenation, e.g., with NMR in on‐flow mode, where solvent signal suppression by special pulse sequences is required. But in the same sense an improved amount of analyte is helpful for off‐line characterization by for example DSC, where the now standard DSC instrumentation and methods may then be used instead of HyperDSC and thus quantitative data can be obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, an enormous potential of this technique becomes obvious when considering the hyphenation of 2D HT‐LC (or HT‐LC) systems with post separation characterization. A direct benefit lies in the on‐line hyphenation, e.g., with NMR in on‐flow mode, where solvent signal suppression by special pulse sequences is required. But in the same sense an improved amount of analyte is helpful for off‐line characterization by for example DSC, where the now standard DSC instrumentation and methods may then be used instead of HyperDSC and thus quantitative data can be obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Two‐component eluents are employed in most LC CC studies. The control of a single‐component eluent strength by means of temperature adjustment is rather difficult . Beaudoin et al have demonstrated that the recovery of polystyrene from bare silica gel depended on the thermodynamic quality of the critical eluent .…”
Section: Resultsmentioning
confidence: 99%
“…This approach was proposed by Skvortsov and Gorbunov and it has been used by numerous authors. . In any case, the sample recovery should be carefully checked before the LC CC method is employed for molecular characterization of complex polymers and complex polymer systems.…”
Section: Discussionmentioning
confidence: 99%
“…By using LCCC‐NMR, blends of PI having different microstructures were separated and analyzed by the authors . Most recently comprehensive two‐dimensional liquid chromatography was coupled on‐line with 1 H‐NMR for the analysis of poly(ethylene oxide)s having different endgroups and chain length distributions …”
Section: Introductionmentioning
confidence: 99%
“…[28] Most recently comprehensive two-dimensional liquid chromatography was coupled on-line with 1 H-NMR for the analysis of poly(ethylene oxide)s having different endgroups and chain length distributions. [29] In the present study PS-b-PI copolymers will be analyzed by the on-line hyphenation of liquid chromatography at critical conditions with 1 H-NMR. The block copolymers were synthesized by sequential living anionic polymerization.…”
Section: Introductionmentioning
confidence: 99%